2022
DOI: 10.3390/plants11202698
|View full text |Cite
|
Sign up to set email alerts
|

The Appeal of Ethnobotanical Folklore Records: Medicinal Plant Use in Setomaa, Räpina and Vastseliina Parishes, Estonia (1888–1996)

Abstract: The historical use of medicinal plants is of special interest because the use of plants for healing is a rapidly changing, highly culture-specific and often need-specific practice, which also depends on the availability of resources and knowledge. To set an example of folkloristic data analysis in ethnobotany, we analyzed texts from the database, HERBA, identifying as many plants and diseases as possible. The research was limited to the Seto, Räpina and Vastseliina parishes in Estonia. The use of 119 taxa belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition to a spatial and socio-political perspective, a diachronic perspective could further contribute to our understanding of the complex dynamics of local ecological knowledge in the Alpine environment. Historical ethnobotanical studies in Europe have often focused on the eastern portion of the continent, where ethnobotanical archival data from the 19th and 20th centuries [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] are frequently available. These studies have generally shown a decrease in wild food plant-centered LEK, while local medicinal plant reports are not only fading but often re-arranged via influences of printed media.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a spatial and socio-political perspective, a diachronic perspective could further contribute to our understanding of the complex dynamics of local ecological knowledge in the Alpine environment. Historical ethnobotanical studies in Europe have often focused on the eastern portion of the continent, where ethnobotanical archival data from the 19th and 20th centuries [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] are frequently available. These studies have generally shown a decrease in wild food plant-centered LEK, while local medicinal plant reports are not only fading but often re-arranged via influences of printed media.…”
Section: Introductionmentioning
confidence: 99%
“…We recommend the following steps in order to increase the resilience of local biocultural diversity and local ecological knowledge in modern (and often highly literate) communities: inclusion of local ecological knowledge in school curricula, in which practical activities need to start as early as elementary school; introduction of ritual elements into the local use of plants (e.g., specific seasonal festivities for wild food plant uses), shared herbal tea making evenings, communal collection events of shared ecological resources, and so forth; and highlighting local historical uses in herbals, cookbooks, and various popularizing activities, stressing the importance of keeping alive local ecological practices and the transfer of knowledge to younger generations. However, the use of “raw” historical data is not suggested, as it needs to be filtered by specialists able to contextualize this type of data (for more details, see Sõukand & Kalle, 2022). …”
Section: Discussionmentioning
confidence: 99%
“…It is considered that modern European (especially medical) ethnobotany is mainly based on ancient herbals and later popularizing books (Leonti, 2011). Yet among the historical data, there are some cases considerably less affected by written knowledge that have a clear connection with the local flora and local understanding of diseases (Kalle et al, 2022; Kalle & Sõukand, 2021; Prakofjewa et al, 2022; Sõukand & Kalle, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The credibility of such historical identifications was also extensively discussed by Łuczaj [ 59 ]. A similar methodology has been used in other historical ethnobotany publications in the same special issue, Historical Ethnobotany: Interpreting the Old Records (e.g., [ 68 , 69 , 70 ]. Identification was facilitated by the voucher specimen collection supplied by Federowski.…”
Section: Methodsmentioning
confidence: 99%